2015
DOI: 10.1111/aji.12425
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Activation Promotes the Secretion of IL-8 Which Enhances the Invasion and Proliferation of Endometrial Stromal Cells in an Autocrine Manner via the FAK Signal Pathway

Abstract: We found that the expression of TLR4 is higher in the eutopic endometrium than the normal endometrium and that ectopic tissue had the highest level of expression. TLR4 activation stimulated IL-8 secretion and the expression of its receptor CXCR1 in ESCs by activating p38/ERK, but not JNK and NK-κB signal pathways. IL-8 could enhance the invasion and proliferation of ESCs through the FAK signal pathway, and these effects could be abolished by an anti-CXCL8 neutralizing antibody or by a FAK inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Luo et al . 12 found that the expression of TLR4 in EU was higher than that in the normal endometrium, and was the highest in EC tissue. TLR4 activation stimulated IL-8 secretion, thus enhancing the invasion and proliferation of endometrial stromal cells through the FAK signal pathway, and these effects could be abolished by an anti-CXCL8 neutralizing antibody or by a FAK inhibitor.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Luo et al . 12 found that the expression of TLR4 in EU was higher than that in the normal endometrium, and was the highest in EC tissue. TLR4 activation stimulated IL-8 secretion, thus enhancing the invasion and proliferation of endometrial stromal cells through the FAK signal pathway, and these effects could be abolished by an anti-CXCL8 neutralizing antibody or by a FAK inhibitor.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies have demonstrated that TLR-mediated activation of immune response may be associated with endometriosis and adenomyosis. It was reported that the expression of TLR4 in the ectopic endometrium of endometriosis was higher than that in the normal endometrium, and the levels of TLR2 and TLR9 mRNAs were higher in the peritoneal effusions of endometriosis than in the non-endometriosis group 12 , 13 .…”
Section: Introductionmentioning
confidence: 94%
“…A variety of molecules activate TLRs on the cell surface (69). TLR4 is best known to be targeted by LPS from bacteria, which leads to cytokine production (70). We therefore analyzed the effect of Fa27 on LPS-activated TLR4 signaling using a reporter cell line and indeed noticed an inhibitory effect of the peptide in the concentration range exerting MLLbcr protection.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study by Luo et al showed enhanced Toll‐like receptor 4 (TLR4) expression the ectopic endometrium and stimulation of IL‐8 secretion by TLR4 ligands in ERK1/2 and p38 MAPK‐dependent manner in endometriotic stromal cells. Moreover, a previous report from our laboratory demonstrated the expression and regulation of T‐ERK1/2 and P‐ERK1/2 in endometrial stromal and glandular cells in women with or without endometriosis .…”
Section: Discussionmentioning
confidence: 99%